SYNTHESIS OF 1,4-DIHYDROPIRIDINE DERIVATIVES IN MICROWAVE FLOW REACTOR - Khrustaleva, Anastassiya; Khrustalev, Dmitriy; Yedrissov, Azamat; Mustafin, Marlen (National Laboratory Astana, 2022)
1,4-Dihydropyridine derivatives (e.g. Nimodipine, Nifedipine, Nitrendipine), which belong to the group of calcium channel blockers, serve as effective drugs in the treatment of cardiovascular diseases. According to the World Health Organization (WHO), this disease class ranks first in terms of the number of deaths worldwide. Considering the unfavorable statistics of mortality from cardiovascular diseases, which is about 17 million people per year, the development of unique, cost- effective methods of obtaining 1,4-dihydropyridine derivatives is an urgent task.
Keywords: Type of access: Embargo; 1,4-Dihydropyridine derivatives